2015
DOI: 10.1111/acer.12592
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Neurotrophin Levels Related to Alcohol Use Disorder in a Young Population Sample

Abstract: These results suggest that elevated neurotrophins are candidate markers for the early stages of alcohol misuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…We found that 9.6% of individuals in our sample had alcohol abuse and/or dependence, which is consistent with previous studies. 6,17 Moreover, in our study, alcohol abuse and/or dependence were associated with male gender, tobacco use, and illicit drug use, and was often comorbid with anxiety disorders, mood disorder, and risk of suicide.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…We found that 9.6% of individuals in our sample had alcohol abuse and/or dependence, which is consistent with previous studies. 6,17 Moreover, in our study, alcohol abuse and/or dependence were associated with male gender, tobacco use, and illicit drug use, and was often comorbid with anxiety disorders, mood disorder, and risk of suicide.…”
Section: Discussionmentioning
confidence: 53%
“…We found that 9.6% of individuals in our sample had alcohol abuse and/or dependence, which is consistent with previous studies. 6,17 Moreover, in our study, alcohol abuse and/or dependence were associated with male gender, tobacco use, and illicit drug use, and was often comorbid with anxiety disorders, mood disorder, and risk of suicide.Several studies have discussed the relationship between AUD and gender, in which males are more likely than females to engage in binge drinking, and therefore, to have AUDs. 18,19 A study performed in 2013 involving 6,478 subjects found that alcohol abuse and/or dependence were more prevalent among males (22.0%) than females (9.8%).…”
mentioning
confidence: 53%
“…2). Notably, studies in humans reported elevated serum GDNF levels in individuals displaying mild to severe AUD (Lhullier et al 2015), but reduced levels in alcohol-dependent individuals experiencing withdrawal (Heberlein et al 2010), supporting the notion that the GDNF system is sensitive to voluntary alcohol intake and that dysregulation of GDNF expression can be detected across species.…”
Section: Gdnf Is An Alcohol-responsive Genementioning
confidence: 71%
“…The family of neurotrophins including nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF), neurotrophin-3 (NT-3), and neurotrophin-4 (NT-4) are important regulators of neural survival, development, function, and plasticity 6,7. BDNF is a critical neurotrophic factor involved in cell growth, survival, and differentiation by regulating synaptic plasticity and neurogenesis 8.…”
Section: Introductionmentioning
confidence: 99%